Impact of Udenafil on Echocardiographic Indices of Single Ventricle Size and Function in FUEL Study Participants. (15th November 2022) - Di Maria, Michael V.; Goldberg, David J.; Zak, Victor; Hu, Chenwei; Lubert, Adam M.; Dragulescu, Andreea; Mackie, Andrew S.; McCrary, Andrew; Weingarten, Angela; Parthiban, Anitha; Goot, Benjamin; Goldstein, Bryan H.; et al.
Abstract : Background: The FUEL trial (Fontan Udenafil Exercise Longitudinal) demonstrated statistical improvements in exercise capacity following 6 months of treatment with udenafil (87.5 mg po BID). The effect of udenafil on echocardiographic measures of single ventricle function in this cohort has not been studied. Methods: The 400 enrolled participants were randomized 1:1 to udenafil or placebo. Protocol echocardiograms were obtained at baseline and 26 weeks after initiation of udenafil/placebo. Linear regression compared change from baseline indices of single ventricle systolic, diastolic and global function, atrioventricular valve regurgitation, and mean Fontan fenestration gradient in the udenafil cohort versus placebo, controlling for ventricular morphology (left ventricle versus right ventricle/other) and baseline value. Results: The udenafil participants (n=191) had significantly improved between baseline and 26 weeks visits compared to placebo participants (n=195) in myocardial performance index ( P =0.03, adjusted mean difference [SE] of changes between groups −0.03[0.01]), atrioventricular valve inflow peak E ( P =0.009, 3.95 [1.50]), and A velocities ( P =0.034, 3.46 [1.62]), and annular Doppler tissue imaging-derived peak e′ velocity ( P =0.008, 0.60[0.23]). There were no significant differences in change in single ventricle size, systolic function, atrioventricular valve regurgitation severity, or mean fenestration gradient. Participants with a dominant left ventricle had significantly more favorable baseline values of indices of single ventricle size and function (lower volumes and areas, E/e′ ratio, systolic:diastolic time and atrioventricular valve regurgitation, and higher annular s′ and e′ velocity). Conclusions: FUEL participants who received udenafil demonstrated a statistically significant improvement in some global and diastolic echo indices. Although small, the changes in diastolic function suggest improvement in pulmonary venous return and/or augmented ventricular compliance, which may help explain improved exercise performance in that cohort. Registration: URL: https://clinicaltrials.gov ; Unique Identifier: NCT02741115.